RNA Sequencing of Murine Norovirus-Infected Cells Reveals Transcriptional Alteration of Genes Important to Viral Recognition and Antigen Presentation - Enosi Tuipulotu, Daniel; Netzler, Natalie E.; Lun, Jennifer H.; Mackenzie, Jason M.; White, Peter A. (Frontiers in Immunology, 2017)
Viruses inherently exploit normal cellular functions to promote replication and survival. One mechanism involves transcriptional control of the host, and knowledge of the genes modified and their molecular function can aid in understanding viral-host interactions. Norovirus pathogenesis, despite the recent advances in cell cultivation, remains largely uncharacterized. Several studies have utilized the related murine norovirus (MNV) to identify innate response, antigen presentation, and cellular recognition components that are activated during infection. In this study, we have used next-generation sequencing to probe the transcriptomic changes of MNV-infected mouse macrophages. Our in-depth analysis has revealed that MNV is a potent stimulator of the innate response including genes involved in interferon and cytokine production pathways. We observed that genes involved in viral recognition, namely IFIH1, DDX58, and DHX58 were significantly upregulated with infection, whereas we observed significant downregulation of cytokine receptors (Il17rc, Il1rl1, Cxcr3, and Cxcr5) and TLR7. Furthermore, we identified that pathways involved in protein degradation (including genes Psmb3, Psmb4, Psmb5, Psmb9, and Psme2), antigen presentation, and lymphocyte activation are downregulated by MNV infection. Thus, our findings illustrate that MNV induces perturbations in the innate immune transcriptome, particularly in MHC maturation and viral recognition that can contribute to disease pathogenesis.